Securing Moral Authority: A Cross-National Analysis of Protestant Engagement in the Implementation of Morality Policies in Western Europe - Olivia Mettang; Eva-Maria Euchner; Lisa Fischer; Jan Menzner (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2023)
Churches have a hard time defending their moral values in the political sphere of an ever more secular and liberal Western Europe. A largely neglected means of navigating this crisis is through the Church's role as a charitable provider during the implementation of morality policies. This paper examines this type of church involvement from a cross-national and cross-sectoral perspective. We describe the activities of Protestant churches in four morality policy areas in three European countries: Germany, England, and Denmark. The variation in religious engagement observed in these areas and countries appear to be driven by the churches' room to maneuver and their policy congruence with state goals, whereas governance capacities are secondary. Thus, the provision of social services can still serve as a means by which Protestant churches can exert moral authority, especially if these social services are related to moral issues.
Keywords: 300; Welfare state; Churches; Protestantism; Religion; Morality policy